Navigating through Tradition and Faith: The Integration of Islamic Values within Baduy Indigenous Wisdom - Hendri Hermawan Adinugraha; Achmad Tubagus Surur; Abdul Khobir; Dliyaudin Achmad; Syauqie Muahammad Marier (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2025)
This study examines the integration of Islamic values within the local wisdom of the Baduy Indigenous community. Its focuses on cultural and religious harmony, utilizing a descriptive-analytical method to explore the socio-cultural and religious dynamics reflected in scientific texts and documents. This research employs a qualitative approach through a systematic review of relevant literature, including scientific journals, books, research reports, academic articles, official documents, and previously published interviews (Mills & Birks, 2017). The primary data consists of literature directly addressing the interaction between Islamic values and Baduy traditions, while secondary sources provide additional context regarding the social, historical, and religious dimensions of the community. The qualitative data analyzed includes narratives, concepts, principles, and interpretations of customary and religious values as practiced by both the Outer and Inner Baduy groups. The thematic analysis was employed following an inductive process, emphasizing textual comprehension alongside a contextual and reflective interpretation of the integration of Islamic principles, while also recognizing the distinctiveness of Baduy customs. Through this methodological framework, the study contributes to the development of a theoretical model for understanding cultural and religious harmony, supported by comprehensive and in-depth literature analysis.